Leveraging artificial intelligence to capture the Singapore rideshare market - VARAKANTHAM, Pradeep (Institutional Knowledge at Singapore Management University, 2018)
BIKE-SHARING programmes face many of the issues encountered by their counterparts in the carsharing world. But in Singapore, there are a number of factors that have a unique impact on the industry. These include the regulatory structure and the significant fines for those companies who do not abide by these regulations. When this is combined with the competitive nature of the industry in one of the world's most dynamic cities, it becomes clear that first movers who leverage machine learning and prediction will come to dominate the industry